PERAN KEPUASAN KERJA DALAM MENINGKATKAN KINERJA DOSEN: STUDI PENGARUH MOTIVASI DI UNIVERSITAS PAMULANG - Sutoro, Moh. (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to examine the influence of motivation on performance through job satisfaction. Motivation is considered a key factor that drives individuals to perform well, and job satisfaction is believed to mediate this relationship. The background of this study is rooted in the understanding that high motivation can lead to increased job satisfaction, which ultimately enhances employee performance. The purpose of this research is to analyze the direct and indirect effects of motivation on performance through job satisfaction using path analysis. A quantitative approach with a survey method was employed. The sample consisted of 290 lecturers from Universitas Pamulang, selected through simple random sampling. Data was collected using a questionnaire focusing on motivation, job satisfaction, and performance. Path analysis was applied to examine the relationships between these variables. The findings show that motivation has a significant positive effect on job satisfaction, which in turn positively impacts performance. This suggests that motivated lecturers tend to be more satisfied with their jobs, leading to improved performance in teaching and other academic responsibilities. Based on these results, it is recommended that universities focus on enhancing motivation among lecturers to foster job satisfaction, which can further improve their performance.